The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/arclin/acq050
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Profile of Executive Function in Girls with Attention-Deficit/Hyperactivity Disorder

Abstract: The majority of research on neurobehavioral functioning among children with Attention-Deficit/Hyperactivity Disorder (ADHD) is based on samples comprised primarily (or exclusively) of boys. Although functional impairment is well established, available research has yet to specify a neuropsychological profile distinct to girls with ADHD. The purpose of this study was to examine performance within four components of executive function (EF) in contemporaneously recruited samples of girls and boys with ADHD. Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 86 publications
(109 reference statements)
8
63
1
2
Order By: Relevance
“…On parent-rated questionnaires, children (Gioia et al, 2002;Shimoni et al, 2012;Siu & Zhou, 2014) as well as adolescents with ADHD (this study; Toplak et al, 2009) consistently show more planning problems than controls. With regard to neurocognitive tasks of planning skills, a discrepancy is visible: On "paper-andpencil," tasks results are mixed in both child and adolescent samples (this study; Galasso et al, 2014;Klorman et al, 1999;Nigg et al, 2002;O'Brien et al, 2010;Qian et al, 2013;Shimoni et al, 2012;Siu & Zhou, 2014;, whereas on computerized tasks, studies consistently show planning deficits in both children and adolescents with ADHD (Gau et al, 2009;Gau & Shang, 2010;Song & Hakoda, 2014;Toplak et al, 2009). In line with the literature, also in our study on parent-rated measures, planning deficits were found, and in our paper-and-pencil neuropsychological measures, we found a significant deficit on one task (BADS) but not on another (D-KEFS).…”
Section: Discussionmentioning
confidence: 69%
“…On parent-rated questionnaires, children (Gioia et al, 2002;Shimoni et al, 2012;Siu & Zhou, 2014) as well as adolescents with ADHD (this study; Toplak et al, 2009) consistently show more planning problems than controls. With regard to neurocognitive tasks of planning skills, a discrepancy is visible: On "paper-andpencil," tasks results are mixed in both child and adolescent samples (this study; Galasso et al, 2014;Klorman et al, 1999;Nigg et al, 2002;O'Brien et al, 2010;Qian et al, 2013;Shimoni et al, 2012;Siu & Zhou, 2014;, whereas on computerized tasks, studies consistently show planning deficits in both children and adolescents with ADHD (Gau et al, 2009;Gau & Shang, 2010;Song & Hakoda, 2014;Toplak et al, 2009). In line with the literature, also in our study on parent-rated measures, planning deficits were found, and in our paper-and-pencil neuropsychological measures, we found a significant deficit on one task (BADS) but not on another (D-KEFS).…”
Section: Discussionmentioning
confidence: 69%
“…Gender differences account for differential expression of ADHD: girls with ADHD commonly display elevated motor overflow and lack of planning, whereas boys with ADHD display greater impairment during conscious, effortful response inhibition (O'Brien et al 2010). This sex-related splaying of symptom expression complicates the issue.…”
Section: Physical Exercise In Adhdmentioning
confidence: 99%
“…are not unique to ADHD, and are common among other emotional and behavioral disorders (e.g., learning disorders, anxiety, depression; American Psychiatric Association 2000), as well as among treatable medical conditions (e.g., thyroid dysfunction, eczema, hearing loss; Feagans et al 1994;Hauser et al 1993;Kooistra et al 1996;Schmitt et al 2009). Moreover, diagnosis of ADHD in girls is even more complicated than it is in boys, due to later age of onset, more subtle clinical manifestations, and limitations associated with the DSM-IV diagnostic nomenclature (Taylor and Keltner 2002;O'Brien et al 2010). Although ADHD presents considerable challenges on its own, diagnosis and treatment is often significantly complicated by cooccurring emotional disorders.…”
mentioning
confidence: 99%